The adult learner : the definitive classic in adult education and human resource development.: the definitive classic in adult education and human resource development. (2020) - Knowles, Malcolm S (Malcolm Shepherd), 1913-1997; Holton, Elwood F, 1957-; Swanson, Richard A, 1942-; Robinson, Petra A
No abstract available